ANALYSIS OF DRUG PLANNING USING THE CONSUMPTION METHOD IN THE PHARMACY INSTALLATION OF FATIMAH ISLAMIC HOSPITAL, CILACAP - muhammad yogie prastowo; Yuniariana Pertiwi; IKRIMATUL CHOIRIYAH (JURNAL PHARMA BHAKTA, 2026)
Background: This study highlights the importance of effective drug management to ensure the availability of safe, high-quality medicines. Ineffective inventory planning may lead to shortages or excess stock, both of which can cause harm. Objective: This study aims to analyze drug planning using the consumption method to improve stock management efficiency. Methods: Data were collected through surveys and analysis of hospital drug consumption patterns. This study emphasizes the integration of pharmaceutical services with drug logistics management as a strategy to enhance the overall quality of health services. Results: Of the 100 drug samples analyzed, 83 required procurement, while 17 did not due to adequate availability. The most frequently consumed drug was acetylcysteine cap 200 mg, with a total usage of 20,607 tablets. Conclusions: Fatimah Islamic Hospital in Cilacap applies the consumption method by considering previous usage data, remaining stock, safety stock, and lead time.